Negative plate, battery and electric equipment

By using nano aluminum trioxide with the most frequency aperture of 2~50nm in the negative electrode active material layer instead of conductive agent, the problems of conductive agent loss and graphite shrinkage during battery circulation are solved, and the circulation and safety performance of the battery are significantly improved.

CN119890312APending Publication Date: 2025-04-25BYD CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411888117.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

During the circulation process, existing batteries form islands due to excessive loss of conductive agent and graphite shrinkage, resulting in a decrease in the circulation and conductivity of the battery.

Method used

The nano aluminum trioxide with the most frequency pore diameter of 2~50nm is added to the negative electrode active material layer to partially or completely replace the conductive agent to improve the wetting efficiency and interface compatibility of the electrolyte.

Benefits of technology

Through the mesoporous structure of nano aluminum trioxide, the cycling performance, first-effect and safety performance of the battery are improved, and excessive consumption of active lithium by conductive agents is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a negative plate, a battery and electric equipment. The negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer arranged on the surface of at least one side of the negative electrode current collector, the negative electrode active material layer comprises nano aluminum oxide, and the most frequency pore diameter of the nano aluminum oxide is 2-50 nm. According to the negative plate disclosed by the invention, the nano aluminum oxide with the most frequency pore diameter of 2-50nm is added into the negative electrode active material layer, so that a conductive agent in the negative electrode active material layer can be partially or completely replaced, excessive loss of the conductive agent to electrolyte and active lithium is avoided, the liquid retention capability of the negative plate is improved, the dynamic performance of the negative plate is improved, and the service life of the negative plate is prolonged. And the battery has good cycle performance and first effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a negative electrode sheet, a battery and an electrical device. Background Art

[0002] In today's era of energy transformation, secondary batteries, as the core of energy storage technology, play a vital role. From portable electronic devices to electric vehicles to large-scale grid energy storage, the widespread use of secondary batteries is driving the global energy system towards a cleaner and more efficient direction. However, the performance of secondary batteries, including their energy density, power density, cycle stability and safety, has always been a common goal pursued by researchers and industry. Among them, conductive agents, as an important component of secondary battery electrode materials, play an indispensable role in improving the overall performance of batteries.

[0003] Commonly used conductive agents in the battery field include conductive carbon black, carbon nanotubes, etc. Among them, conductive carbon black has low mechanical strength. During use, as the negative electrode material shrinks and expands, the contact area between the negative electrode material particles is likely to decrease, and even the material may fall off, resulting in the attenuation of battery cycle performance. Linear conductive agents such as carbon nanotubes and carbon fibers, due to their high specific surface area, will cause serious side reactions between the conductive agent and the electrolyte, thereby consuming active lithium and electrolyte, resulting in a significant reduction in battery capacity and coulomb efficiency. If the amount of conductive agent added to the negative electrode sheet is reduced, it is easy to cause the graphite to shrink during the battery charge and discharge cycle to form graphite islands, making it difficult for the particles to contact each other, thereby deteriorating the battery's cycle performance and conductivity.

[0004] Therefore, how to avoid the addition of conductive agents in the negative electrode sheet affecting the battery cycle performance and the loss of active lithium is a technical problem that needs to be solved urgently in this field. Summary of the invention

[0005] The present invention provides a negative electrode sheet, a battery and an electric device. The negative electrode sheet of the present invention adds nano-aluminum oxide with a most frequent pore size of 2 to 50 nm in the negative electrode active material layer, which can partially or completely replace the conductive agent in the negative electrode active material layer, thereby avoiding excessive loss of electrolyte and active lithium by the conductive agent, improving the liquid retention capacity of the negative electrode sheet, and improving the dynamic performance of the electrode sheet, so that the battery has good cycle performance and first effect.

[0006] A first aspect of the present invention provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector, wherein the negative electrode active material layer comprises nano-aluminum oxide, and the mode pore size of the nano-aluminum oxide is 2-50 nm.

[0007] The negative electrode sheet as described above, wherein the nano-aluminum oxide is a secondary particle formed by accumulation of primary particles;

[0008] The particle size of the primary particles is 5 to 800 nm.

[0009] The negative electrode sheet as described above, wherein the negative electrode active material layer comprises, by mass percentage, 88% to 98% of negative electrode active material, 0.01% to 5% of conductive agent, 0.01% to 2% of nano-aluminum oxide, 0.5% to 5% of thickener, and 0.5% to 5% of binder.

[0010] The negative electrode sheet as described above, wherein the negative electrode active material layer comprises 0.1% to 1% of a conductive agent and 0.1% to 1% of nano-aluminum oxide in terms of mass percentage.

[0011] In the negative electrode sheet as described above, the conductive agent includes one or more of conductive carbon black, carbon nanotubes, graphene, conductive graphite, and carbon fiber.

[0012] The negative electrode sheet as described above, wherein the negative electrode active material comprises one or more of carbon materials, silicon-based materials, tin-based materials, and lithium titanate materials.

[0013] The negative electrode sheet as described above, wherein the surface of the negative electrode active material layer away from the negative electrode current collector is the first surface, and the surface of the negative electrode active material layer close to the negative electrode current collector is the second surface;

[0014] The mass content of nano-aluminum oxide on the first surface is less than the mass content of nano-aluminum oxide on the second surface.

[0015] The negative electrode sheet as described above, wherein in the thickness direction of the negative electrode active material layer from the second surface to the first surface, the mass content of the nano-aluminum oxide decreases gradually.

[0016] A second aspect of the present invention provides a battery, comprising the negative electrode sheet as described above.

[0017] A third aspect of the present invention provides an electrical device comprising the battery as described above.

[0018] The implementation of the present invention has at least the following beneficial effects:

[0019] 1) The present invention adds nano-aluminum oxide with a most frequent pore size of 2 to 50 nm to the negative electrode active material layer. Its unique mesoporous structure gives the material a high affinity with the electrolyte and excellent wettability. When applied to the negative electrode of a lithium-ion battery, this nanomaterial can significantly improve the electrolyte infiltration efficiency, optimize the interface compatibility between the negative electrode and the electrolyte, and enhance the ionic conductivity, thereby improving the overall kinetic behavior of the battery. At the same time, the pores and channels inside the nano-aluminum oxide provide a smooth penetration path for the electrolyte, ensuring that the electrolyte can be easily filled in the pores of the material, which not only shortens the transmission distance of lithium ions, but also promotes the rapid diffusion of lithium ions in the electrode material, thereby reducing the resistivity and cycle performance of the electrode.

[0020] 2) Aluminum oxide has good mechanical strength, which not only helps to make the lithium ion transmission during the battery charging and discharging process fast and uniform, but also improves the polarization of the electrode and the battery.

[0021] 3) Compared with conductive agents, aluminum oxide is a low dielectric constant material. Using it to partially or completely replace the conductive agent and add it to the negative electrode sheet can avoid excessive consumption of active lithium in the electrolyte caused by SEI growth on the surface of the conductive material, thereby improving the initial efficiency and cycle stability of the battery.

[0022] 4) Aluminum oxide itself is non-toxic and has good heat resistance and is non-flammable. Adding it to the negative electrode sheet is also beneficial to improving the safety performance of the battery. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] A first aspect of the present invention provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector, wherein the negative electrode active material layer comprises nano-aluminum oxide, and the mode frequency pore size of the nano-aluminum oxide is 2-50 nm.

[0025] In the present invention, the most frequent aperture refers to the aperture value corresponding to the highest point in the aperture frequency distribution curve of nano-aluminum oxide.

[0026] Aluminum oxide with a most frequent pore size of 2~50nm has a unique mesoporous structure. This structural characteristic gives the material a high affinity with the electrolyte and excellent wettability. After adding the negative electrode active material, it can significantly improve the electrolyte infiltration efficiency and optimize the interface compatibility between the negative electrode sheet and the electrolyte. In addition, the pores of the mesoporous structure provide a smooth penetration path for the electrolyte, ensuring that the electrolyte can be filled between the pores of alumina, shortening the transmission distance of lithium ions, promoting the diffusion of lithium ions in the battery material, and reducing the electrode resistivity and battery cycle performance.

[0027] In addition, alumina has good mechanical strength, which is beneficial to making the lithium ion transmission during the battery charging and discharging process fast and uniform, and improving the polarization of the electrode and the battery; in addition, compared with the conductive agent, alumina is a low dielectric constant material. Using it to partially or completely replace the conductive agent and add it to the negative electrode can avoid excessive consumption of active lithium in the electrolyte caused by the growth of SEI on the surface of the conductive material, thereby improving the battery's initial efficiency and cycle stability.

[0028] It is worth mentioning that aluminum oxide itself is non-toxic and has good heat resistance and is non-flammable. Adding it to the negative electrode sheet is also beneficial to improving the safety performance of the battery.

[0029] The nano aluminum oxide of the present invention can be a mesoporous material with pore diameters ranging from 2 to 50 nm, a material with graded micropores (pore diameter <2 nm) plus mesopores, a material with graded mesopores plus large pores (>50), or a material with graded micropores plus mesopores plus large pores, as long as the value of the most frequent pore diameter is within the range of 2 to 50 nm.

[0030] For nano-alumina with the above-mentioned most frequent pore size distribution range, it is possible to directly obtain nano-alumina products that meet the requirements through commercial purchase, or to adjust the process so that the most frequent pore size of alumina meets the above range, for example, through heat treatment, mechanical grinding, chemical acid-base etching, complexing agent etching, gas plasma etching, etc.

[0031] Generally, nano-aluminum trioxide raw materials that meet the above pore size distribution range can be selected for the preparation of negative electrode sheets. After the electrode sheet preparation process, the pore size distribution, particle size distribution and other parameter characteristics of nano-aluminum trioxide are basically the same as before preparation. In order to verify whether the electrode sheet processing process will affect the parameter characteristics of nano-aluminum trioxide, the negative electrode sheet can be placed in a hydrochloric acid solution, and the dissolution process can be accelerated by stirring or ultrasonic treatment. After removing the negative electrode current collector and other components in the negative electrode active material layer except the negative electrode active material and the SEI film, the solution and the insoluble components are filtered or centrifuged. Dry the insoluble components and grind them into fine particles of a certain size, then mix them with an appropriate amount of solvent or dispersant, place them in an ultrasonic bath or use an ultrasonic probe for ultrasonic treatment to form a uniform suspension. During the ultrasonic treatment process, due to the different characteristics of negative electrode active materials such as graphite and aluminum trioxide nanoparticles, tiny aggregation and dispersion phenomena will occur. After the ultrasound is completed, the sample is centrifuged and the centrifugal rate is adjusted to separate the negative electrode active material from the aluminum trioxide nanoparticles. The aluminum oxide nanoparticles were dried, ground and pulverized, and then subjected to corresponding characterization tests.

[0032] In a specific embodiment, the nano-aluminum oxide is a secondary particle formed by the accumulation of primary particles; wherein the particle size of the primary particles is 5-800 nm.

[0033] The particle size of the primary particles can be obtained by using a scanning electron microscope to detect the morphology of nano-aluminum oxide. When the particle size of the primary particles is within the above range, the internal pore structure and distribution of the electrode can be adjusted to make the pore size more uniform or form a graded pore structure, which is more conducive to the absorption and retention of liquid by the electrode, thereby improving the dynamic performance of the battery.

[0034] Illustratively, the particle size of the primary particles can be 5 nm, 10 nm, 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm or a range consisting of any two of the above values.

[0035] In a preferred embodiment, the negative electrode active material layer includes 88% to 98% of negative electrode active material, 0.01% to 5% of conductive agent, 0.01% to 2% of nano aluminum oxide, 0.5% to 5% of thickener, and 0.5% to 5% of binder by mass percentage. When the negative electrode sheet includes the above components by mass percentage, it is beneficial to include sufficient negative electrode active material in the negative electrode active material layer so that the negative electrode sheet maintains a high gram capacity, and also enables the negative electrode sheet to have good liquid retention capacity and lithium ion conductivity.

[0036] More preferably, the negative electrode active material layer includes 0.1% to 1% of a conductive agent and 0.1% to 1% of nano-aluminum trioxide in terms of mass percentage. Experimental verification has shown that when the negative electrode active material layer includes the above-mentioned conductive agent and nano-aluminum trioxide, the negative electrode sheet can have a sufficient amount of conductive agent to make the battery have good conductivity, and the battery's liquid retention capacity can be fully improved, so that the battery has both excellent dynamic performance and cycle performance.

[0037] The present invention does not specifically limit the type of the conductive agent, which can be selected from conductive agents conventionally used in the art, including but not limited to one or more of conductive carbon black, carbon nanotubes, graphene, and carbon fibers.

[0038] Furthermore, the conductive carbon black may be one or more of acetylene black, furnace black, channel black, thermal black, lamp black, and Ketjen black; the carbon nanotube may be a combination of one or more carbon nanotubes with a diameter ranging from 1 to 100 nm and a diameter length ranging from 50 nm to 100 μm; the graphene may be a combination of one or more graphenes with a layer number of 1 to 1000 layers; and the conductive graphite may be artificial graphite and / or natural graphite.

[0039] The present invention does not specifically limit the type of negative electrode active material, which can be selected from negative electrode active materials conventionally used in the art, including but not limited to one or more of carbon materials, silicon-based materials, tin-based materials, and lithium titanate materials.

[0040] Furthermore, the carbon material may be one or more of artificial graphite, natural graphite, soft carbon, hard carbon, mesophase carbon microspheres, and carbon fibers; the silicon-based material may be one or more of elemental silicon, silicon oxide, silicon alloy, composite silicon, and silicon-carbon material; the tin-based material may be tin oxide and / or tin alloy.

[0041] The present invention does not limit the type of thickener in the negative electrode sheet, and the thickener can be selected from the thickeners conventionally used in the art, including but not limited to one or more of carboxymethyl cellulose sodium (CMC-Na), carboxymethyl cellulose lithium (CMC-Li), polyacrylic acid (PAA), polyvinyl alcohol (PVA), polyacrylonitrile (PAN), and natural rubber (NR).

[0042] The present invention does not specifically limit the type of binder in the negative electrode sheet, which can be selected from binders conventionally used in the art, including but not limited to one or more of polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer, polytetrafluoroethylene, polyacrylonitrile, polypropylene carbonate, styrene-butadiene rubber (SBR), nitrile rubber, polyethylene oxide, and ethylene oxide-propylene oxide copolymer.

[0043] The negative electrode active material layer of the present invention can be arranged on one surface of the negative electrode current collector or on both surfaces. The present invention does not specifically limit the type of the negative electrode current collector, which can be selected from the negative electrode current collectors conventionally used in the art, such as copper foil or carbon-coated copper foil, more preferably carbon-coated copper foil.

[0044] In the present invention, the surface of the negative electrode active material layer away from the negative electrode current collector is the first surface, and the surface close to the negative electrode current collector is the second surface. In a preferred embodiment, the mass content of nano-aluminum oxide on the first surface is less than the mass content of nano-aluminum oxide on the second surface.

[0045] It can be understood that the closer to the negative electrode current collector, the more difficult it is to wet the negative electrode active material layer. Therefore, according to this rule, the present invention makes the mass content of nano-aluminum oxide on the second surface of the negative electrode active material layer close to the negative electrode current collector greater than the mass content of the first surface away from the negative electrode current collector, so that the negative electrode active material layer as a whole is easier to wet, and also ensures that the negative electrode active material layer has good conductivity.

[0046] In a specific embodiment, the negative electrode sheet having the above distribution form can be prepared by the following method:

[0047] Two negative electrode slurries containing different contents of nano-aluminum trioxide are prepared respectively, and the two slurries are coated on the surface of the negative electrode current collector by a double-layer coating process, so that the negative electrode slurry with a higher content of nano-aluminum trioxide is close to one side of the negative electrode current collector, and the negative electrode slurry with a lower content of nano-aluminum trioxide is away from one side of the negative electrode current collector. The surface density of the two sides is controlled to be 1:1. After drying and rolling, a negative electrode sheet with a mass content of nano-aluminum trioxide on the first surface being less than the mass content of nano-aluminum trioxide on the second surface can be obtained.

[0048] More preferably, the mass content of nano-aluminum oxide decreases gradually in the thickness direction of the negative electrode active material layer from the second surface to the first surface. This embodiment maximizes the design of the mass content of nano-aluminum oxide in the negative electrode active material layer according to the wetting law of the negative electrode active material layer, so that the content of nano-aluminum oxide gradually decreases from close to the current collector to away from the current collector, further reducing the wetting difficulty of the negative electrode active material layer and improving the conductivity.

[0049] In a specific embodiment, it can be achieved by regulating the slurry coating process. For example, different concentrations of negative electrode slurries including nano-aluminum oxide can be configured, and the slurry can be coated on the surface of the negative electrode current collector in the form of a gradient increase. After the first layer of slurry is dried, the next layer of slurry is coated, or the solid content of the slurry and the standing time of the slurry on the negative electrode current collector are controlled, and the gradient distribution of nano-aluminum oxide on the negative electrode active material layer can be achieved by using gravity sedimentation.

[0050] A second aspect of the present invention provides a battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet comprises the negative electrode sheet provided by the first aspect of the present invention.

[0051] Since the battery of the present invention comprises the negative electrode sheet, the battery has excellent cycle life and initial efficiency.

[0052] The battery of the present invention includes, but is not limited to, a lithium ion battery or a sodium ion battery.

[0053] The present invention does not specifically limit the composition of the positive electrode sheet, which can refer to the conventional positive electrode sheet composition in the art. Specifically, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector.

[0054] The present invention does not specifically limit the composition of the positive electrode current collector, which can be selected from positive electrode current collectors commonly used in the art, such as aluminum foil.

[0055] In a specific embodiment, the positive electrode active material layer includes a positive electrode active material, a conductive agent, and a binder.

[0056] When the battery is a sodium ion battery, the positive electrode active material includes but is not limited to one or more of transition metal oxides, polyanionic compounds, organic polymers, and Prussian blue materials.

[0057] When the battery is a lithium-ion battery, the positive electrode active material includes but is not limited to one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and olivine-structured lithium-containing phosphate.

[0058] The types of conductive agent and binder in the positive electrode sheet can refer to the selectable range of conductive agent and binder in the negative electrode sheet, and will not be repeated here.

[0059] The composition of the diaphragm may also refer to the conventional diaphragm composition in the art. For example, the diaphragm may be a composite membrane of one or more of polypropylene, polyethylene, and polyvinylidene fluoride.

[0060] The present invention does not specifically limit the type of electrolyte, which can be selected from electrolytes commonly used in the art and will not be described in detail here.

[0061] The present invention does not impose any particular limitation on the method for preparing the battery, and the battery can be prepared by referring to conventional methods in the art.

[0062] For example, in a specific embodiment, a battery can be prepared by the following steps:

[0063] The positive electrode sheet, separator and negative electrode sheet are placed in sequence, and then the battery cell assembly is obtained by winding or stacking, and then the battery is obtained after processes such as liquid injection, formation, and capacity division.

[0064] The third aspect of the present invention further provides an electric device, comprising the battery as described above. The present invention does not specifically limit the electric device, and it can be any electric device comprising the battery, including but not limited to mobile phones, portable devices, laptop computers, electric bicycles, electric cars, electric toys, energy storage devices, etc.

[0065] The negative electrode sheet and the battery provided by the present invention will be specifically introduced below through specific embodiments.

[0066] Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, conventional materials and conventional instruments in the art and can be obtained commercially. The reagents involved can also be synthesized by conventional methods in the art.

[0067] In the following embodiments and comparative examples, the most frequent pore size test method of nano Al2O3 is the BET static method, which specifically includes the following steps: placing the sample in a sample tube of an adsorption instrument, and pre-treating the sample to remove impurities and moisture on the surface, then contacting the sample with an inert gas (such as nitrogen) under a series of known relative pressures to reach adsorption equilibrium, testing the adsorption amount under different relative pressures, and calculating the specific surface area and pore size distribution of the material based on these data using the BET theory.

[0068] In the following embodiments and comparative examples, the primary particle size of the nano-Al2O3 material can be obtained by taking microscopic morphology photographs of the material using a scanning electron microscope. The magnification is based on the ability to clearly observe the primary particles. The diameters of all primary particles within the field of view are measured and the average value is calculated to obtain the primary particle size of the nano-Al2O3 material.

[0069] Example 1

[0070] This embodiment provides a negative electrode sheet and a battery, and the preparation method thereof is as follows:

[0071] 1. Preparation of negative electrode sheet

[0072] 96wt% of artificial graphite as negative electrode active material, 0wt% of conductive agent carbon black (SP), 1wt% of nano Al2O3 (with a most frequent pore size of 28nm), 1wt% of thickener CMC, and 2wt% of binder SBR are uniformly mixed to obtain a powder, the powder and deionized water are stirred into a negative electrode slurry using a homogenizer and coated on both sides of the copper foil at one time, and a negative electrode sheet with a negative electrode active material layer thickness of 183μm is obtained after drying, rolling, and sheeting.

[0073] 2. Preparation of batteries

[0074] 1) Preparation of positive electrode

[0075] The positive electrode active material lithium iron phosphate (LiFePO4), conductive agent (CNT), and binder (PVDF) are mixed in a ratio of 97:1:2, and the powder and NMP are stirred into positive electrode slurry in a homogenizer and evenly coated on both sides of the aluminum foil. After drying, rolling, and sheeting, the positive electrode sheet is obtained.

[0076] 2) Preparation of electrolyte

[0077] Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and LiPF6 is added therein to dissolve to obtain an electrolyte with a LiPF6 concentration of 1 mol / L.

[0078] 3) Battery assembly

[0079] The negative electrode sheet, polypropylene separator and positive electrode sheet prepared above are placed in sequence, stacked to obtain a stacked core, and the stacked core is placed on an outer packaging foil, and the prepared electrolyte is injected. After the formation, capacity separation and other processes, a battery with a capacity of 1.7Ah is obtained.

[0080] Examples 2 to 10 and Comparative Examples 1 to 3

[0081] The preparation methods of the negative electrode sheets and batteries of Examples 2 to 10 and Comparative Examples 1 to 3 are basically the same, except that the amount of conductive agent added in the negative electrode sheet, the amount of aluminum oxide added, the most frequent pore size of aluminum oxide, and the primary particle size of aluminum oxide are different from those in Example 1, as shown in Table 1.

[0082] It should be noted that when the sum of the added amounts of the conductive agent and Al2O3 is not 1wt%, the content of the artificial graphite as the negative electrode active material is adjusted so that the sum of the artificial graphite, the conductive agent carbon black, nano-Al2O3, CMC and SBR is 100wt%.

[0083] Table 1

[0084]

[0085] Embodiment 11

[0086] This embodiment provides a negative electrode sheet and a battery, wherein a method for preparing the negative electrode sheet comprises the following steps:

[0087] 1) 96 wt% of artificial graphite as a negative electrode active material, 0.6 wt% of carbon black as a conductive agent, 0.4 wt% of nano-Al2O3 (with a mode pore size of 28 nm and a primary particle size of 32 nm), 1 wt% of CMC as a thickener, and 2 wt% of SBR as a binder are uniformly mixed to obtain a powder, and the powder is stirred with deionized water using a homogenizer to obtain a first negative electrode slurry;

[0088] 96 wt% of artificial graphite as a negative electrode active material, 0.4 wt% of carbon black as a conductive agent, 0.6 wt% of nano-Al2O3 (with a mode pore size of 28 nm and a primary particle size of 32 nm), 1 wt% of CMC as a thickener, and 2 wt% of SBR as a binder are uniformly mixed to obtain a powder, and the powder is stirred with deionized water using a homogenizer to obtain a second negative electrode slurry;

[0089] 2) A double-layer coating process was used to coat the first negative electrode slurry and the second negative electrode slurry on both sides of the copper foil, so that the first negative electrode slurry was coated on the surface of the copper foil, and the second negative electrode slurry was coated on the first negative electrode slurry, and the coating surface density of the first negative electrode slurry and the second negative electrode slurry was controlled to be 1:1. After drying, rolling and sheeting, the negative electrode sheets with the thickness of the first negative electrode active material layer and the second negative electrode active material layer being 91.5 μm and 91.5 μm respectively were obtained.

[0090] The preparation method of the battery is basically the same as that of Example 1, except that the negative electrode sheet is replaced with the negative electrode sheet of this example.

[0091] Example 12

[0092] This embodiment provides a negative electrode sheet and a battery, wherein a method for preparing the negative electrode sheet comprises the following steps:

[0093] 1) 96 wt% of artificial graphite as a negative electrode active material, 0.1 wt% of carbon black as a conductive agent, 0.9 wt% of nano-Al2O3 (with a mode pore size of 28 nm and a primary particle size of 32 nm), 1 wt% of CMC as a thickener, and 2 wt% of SBR as a binder are uniformly mixed to obtain a powder, and the powder is stirred with deionized water using a homogenizer to obtain a first negative electrode slurry;

[0094] 96 wt% of artificial graphite as a negative electrode active material, 0.4 wt% of carbon black as a conductive agent, 0.6 wt% of nano-Al2O3 (with a mode pore size of 28 nm and a primary particle size of 32 nm), 1 wt% of CMC as a thickener, and 2 wt% of SBR as a binder are uniformly mixed to obtain a powder, and the powder is stirred with deionized water using a homogenizer to obtain a second negative electrode slurry;

[0095] 96 wt % of artificial graphite as a negative electrode active material, 1 wt % of carbon black as a conductive agent, 1 wt % of CMC as a thickener, and 2 wt % of SBR as a binder are uniformly mixed to obtain a powder, and the powder is stirred with deionized water using a homogenizer to obtain a third negative electrode slurry;

[0096] 2) coating a first negative electrode slurry on a surface of a copper foil, and drying it to form a first negative electrode active material layer; coating a second negative electrode slurry on a surface of the first negative electrode active material layer, and drying it to form a second negative electrode active material layer; coating a third negative electrode slurry on a surface of the second negative electrode active material layer, and drying it to form a third negative electrode active material layer, and rolling and sheeting to obtain a negative electrode sheet, wherein the coating surface density of the first negative electrode slurry, the second negative electrode slurry and the third negative electrode slurry is 1:1:1, and the thicknesses of the first negative electrode active material layer, the second negative electrode active material layer and the third negative electrode active material layer are 61 μm, 61 μm and 61 μm, respectively.

[0097] The preparation method of the battery is basically the same as that of Example 1, except that the negative electrode sheet is replaced with the negative electrode sheet of this example.

[0098] Comparative Example 4

[0099] This comparative example provides a negative electrode sheet and a battery, and the preparation method thereof is basically the same as that of Example 9, except that nano-Al2O3 is replaced by nano-SiO2.

[0100] Test Case

[0101] 1. Negative electrode liquid retention capacity

[0102] Test method: The negative electrode sheets obtained in the above embodiments and comparative examples were baked at 120°C for 12 h, and the mass of the negative electrode sheets after baking was recorded. Under a 25°C environment, the baked negative electrode sheets were soaked in electrolyte for 48 h and then taken out, and the mass of the negative electrode sheets after soaking in electrolyte was recorded. The liquid retention amount of the negative electrode sheets was calculated, and the calculation formula of the liquid retention amount was: liquid retention amount = (mass of the negative electrode sheet after soaking in electrolyte - mass of the negative electrode sheet after baking) / mass of the coating of the negative electrode sheet. The test results are shown in Table 2.

[0103] 2. Resistivity

[0104] Test method: The negative electrode sheets obtained in the above embodiments and comparative examples were laid flat in the test chamber of the resistance meter, and the test probe was brought into contact with the surface of the negative electrode sheet to perform the test and read the resistivity of the negative electrode sheet. The test results are shown in Table 2.

[0105] 3. First effect

[0106] Test method: At 25°C, the batteries obtained in the above examples and comparative examples were charged to 100% SOC at constant current and constant voltage, aged at 45°C for 24 hours, and discharged to 0% SOC at 0.1C constant current, and the charging and discharging capacities were recorded. The first charge and discharge efficiency was calculated, and the first efficiency of the whole battery = discharge capacity / charge capacity × 100%. The test results are shown in Table 2.

[0107] 4. Cycle life

[0108] Test method: Charge the battery at 1C to 3.8V at 45°C, leave it for 10 min, then discharge it at 1C to 2.0V, cycle it 500 times, and record the capacity retention rate; capacity retention rate after 500 cycles (%) = discharge specific capacity after 500 cycles / discharge specific capacity after the third cycle × 100%. The test results are shown in Table 2.

[0109] 5. Low temperature -10℃ DC internal resistance test (DCIR)

[0110] Test method: calibrate the battery capacity at 25°C, 0.2C charge and discharge, then charge to 50% SOC at 0.2C, then place the battery at -10°C, charge at 1 / 3C for 30s, record the termination voltage and termination current of each process, and finally calculate the DC internal resistance DCIR of the process. The calculation formula is: DCIR= (V2-V1)×3; V1 is the voltage at 30s, and V2 is the termination voltage of the previous step.

[0111] The test results are shown in Table 2.

[0112] Table 2

[0113]

[0114] 1) From the comparison of Examples 1 to 4, it can be seen that the total amount of conductive agent and aluminum oxide nanomaterial added remains constant. With the decrease of the conductive agent content and the increase of the nano aluminum oxide content, the liquid retention of the electrode increases, the initial efficiency of the battery is improved, and the resistivity of the electrode increases. In particular, when the conductive agent content of Example 1 is 0, the resistivity of the electrode increases significantly, resulting in a higher DC internal resistance of the battery at -10°C, which results in a relatively low cycle life of the battery.

[0115] Among them, the negative electrode sheets of Examples 2 to 3 all contain a certain amount of conductive agent and aluminum oxide, which can make the electrode sheets have better comprehensive performance in terms of liquid retention, resistivity, battery first efficiency, cycle performance and DCIR.

[0116] 3) From the comparison of Examples 5, 6, 9 and Comparative Examples 2 and 3, it can be seen that with the increase of the most frequent pore size of nano alumina, the particle size of its primary particles also decreases accordingly. When the most frequent pore size of nano alumina is less than 2nm (Comparative Example 3) or greater than 50nm (Comparative Example 4), the liquid retention capacity of the electrode is significantly lower, and due to the absence of the addition of a conductive agent, the resistivity of the electrode is also higher. Although the battery still has a higher first efficiency, its DCIR performance and cycle capacity retention rate are significantly poor. With the increase of the most frequent pore size of nano alumina in the range of 2~50nm, the liquid retention capacity of the electrode shows a trend of first decreasing and then increasing, and the resistivity of the electrode also shows a trend of first increasing and then decreasing. The first efficiency of the battery, the capacity retention rate after 500 cycles, and the DCIR are basically the same, with no significant changes.

[0117] 4) From the comparison of Examples 7, 8, 9, and 10, it can be seen that when the electrode does not contain a conductive agent, the battery has a higher initial efficiency, and as the content of nano-aluminum oxide in the electrode increases, the liquid retention of the electrode increases, while the resistivity and DCIR of the electrode are higher. The cycle performance of the battery is also generally inferior to the effect of using a mixture of a conductive agent and nano-aluminum oxide.

[0118] 5) From the comparison between Examples 1 to 4 and 11 to 12, it can be seen that compared with a single-layer coating, by double-layer coating or triple-layer coating, and by reducing the gradient of the nano-aluminum oxide content located at the surface layer of the negative electrode active material layer to the nano-aluminum oxide content located at the bottom layer of the negative electrode active material layer, the electrode has a higher liquid retention capacity, and the resistivity of the electrode is relatively low. In addition, the comprehensive performance of the first efficiency, cycle capacity retention rate and DCIR is more excellent. As the number of coating layers increases, the liquid absorption and retention capacity of the electrode, the resistivity of the electrode and the comprehensive performance optimization of the battery are more significant.

[0119] 6) From the comparison between Example 1 and Comparative Example 1, it can be seen that when neither a conductive agent nor nano-aluminum oxide is added to the electrode, the liquid retention capacity of the electrode is significantly reduced, the resistivity of the electrode is also significantly increased, the capacity retention rate of the battery after 500 cycles is significantly lower, and the DCIR value of the battery is significantly higher.

[0120] 7) From the comparison between Example 9 and Comparative Example 4, it can be seen that after replacing nano-aluminum oxide with nano-silicon dioxide, although the liquid retention rate and resistivity of the electrode are basically the same, the cycle performance and DCIR performance are relatively poor.

[0121] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A negative electrode sheet, characterized in that: The invention comprises a negative electrode current collector and a negative electrode active material layer arranged on at least one side surface of the negative electrode current collector. The negative electrode active material layer comprises nano-aluminum oxide, and the mode aperture of the nano-aluminum oxide is 2-50nm.

2. The negative electrode sheet according to claim 1, characterized in that: The nano-aluminum oxide is a secondary particle formed by the accumulation of primary particles; The particle size of the primary particles is 5 to 800 nm.

3. The negative electrode sheet according to claim 1 or 2, characterized in that: The negative electrode active material layer includes, by mass percentage, 88% to 98% of negative electrode active material, 0.01% to 5% of conductive agent, 0.01% to 2% of nano-aluminum oxide, 0.5% to 5% of thickener, and 0.5% to 5% of binder.

4. The negative electrode sheet according to claim 3, characterized in that: The negative electrode active material layer includes 0.1% to 1% of a conductive agent and 0.1% to 1% of nano-aluminum oxide in terms of mass percentage.

5. The negative electrode sheet according to claim 3 or 4, characterized in that: The conductive agent includes one or more of conductive carbon black, carbon nanotubes, graphene, conductive graphite, and carbon fiber.

6. The negative electrode sheet according to any one of claims 3 to 5, characterized in that: The negative electrode active material includes one or more of carbon materials, silicon-based materials, tin-based materials, and lithium titanate materials.

7. The negative electrode sheet according to claim 1, characterized in that: The surface of the negative electrode active material layer away from the negative electrode current collector is a first surface, and the surface of the negative electrode active material layer close to the negative electrode current collector is a second surface; The mass content of nano-aluminum oxide on the first surface is less than the mass content of nano-aluminum oxide on the second surface.

8. The negative electrode sheet according to claim 7, characterized in that: In the thickness direction of the negative electrode active material layer from the second surface to the first surface, the mass content of the nano-aluminum oxide decreases gradually.

9. A battery, characterized in that: A negative electrode sheet comprising any one of claims 1 to 8.

10. An electrical device, characterized in that: A battery comprising the battery of claim 9.

Citation Information

Cited By

  • Negative electrode material composition, negative electrode plate and sodium ion battery

    CN121076133A